Decomposition Analysis of Anemia Among Women of Reproductive Age in Northeast India: Evidence from NFHS-4 and NFHS-5 - Sabrina Sultana Rahman; Ruma Talukdar (National Journal of Community Medicine)
Background: Anemia, characterized by low red blood cell and haemoglobin levels, affects 1.62 billion people globally. It is a major public health concern among reproductive-age women in India, particularly in Northeast regions, where prevalence remains high. The study aims to analyze trends in anemia among reproductive-age women in Northeast India, drawing on data from the NFHS. By employing decomposition analysis, the research seeks to evaluate the extent to which socioeconomic, demographic, and dietary factors have contributed to changes in anemia prevalence over time.